IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN MENGGUNAKAN GOOGLE CLASSROOM DI SMPN 13 MALANG - Agnes Sania Rizmawati; Nur Hasan; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study uses a qualitative approach with a qualitative descriptive method. The purpose of this study is to describe how the learning process using google classroom or the same as various models and forms of application in doing google classroom learning in learning Islamic religious education at SMPN 13. In this study, the researcher acts as an instrument as well as a data collector. The results of the research that have been carried out are 1) How to implement an Islamic religious education learning system using Google Classroom 2) How to implement learning through Google Classroom 3) Evaluation in the learning process of Islamic religious education using Google Classroom